Need Assessment : Development of Massive Open Online Courses Video-Based Competency Training Management - Andi Mardiana Paduppai; Nerru Pranuta Murnaka; Fransiskus Ransus (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
PP PAUD and Central Java Dikmas are tasked with overseeing all early childhood education institutions and community education throughout the Central Java region. This study aims to analyze the process of planning, organizing, implementing, and evaluating the massive open online course (MOOC) that took place at PP PAUD and Dikmas Central Java during the COVID-19 pandemic. This research is quantitative research with a descriptive approach. The sample in this study were PAUD teachers throughout Central Java and MOOC Education and Training supervisors at PP PAUD and Dikmas Central Java. Sample selection was carried out using the Simple Random Sampling method. The research instruments used were questionnaires, documentation, and interviews that experts have validated. Data analysis techniques used descriptive statistical analysis and percentages for questionnaire results and verbal analysis for interviews and documents. Based on the results and analysis of the discussion, we observe that MOOC in PP PAUD and Central Java Dikmas is going well. However, the content developed must still be adapted to the scope of PP PAUD. The materials in MOOCs need to be entirely focused on the essential competencies and core competencies of PP PAUD. Therefore, it is necessary to manage and develop video-based training through MOOCs.